Physiological and biomechanical aspects of orienteering - Creagh, U.; Reilly, T. (Sports Medicine, 1997)
Orienteering is an endurance running event which differs from other running sports both in its cognitive element and in the type of terrain encountered. The demands of overcoming this terrain are not manifest in significant differences between orienteers and road runners in somatotype, though elite female orienteers have consistently been shown to have higher levels of adiposity (> 19%) than elite road runners. High aerobic power in orienteers (up to 63 and 76 ml/kg/min in women and men, respectively) is coupled with lower anaerobic performance. While leg strength is generally not high when compared with other athletic specialties, female orienteers have relatively good leg flexion strength. The energy cost of running is greatly increased in rough terrain. Oxygen cost was 26% higher while running in a forest when compared with road running. Biomechanical differences in stride pattern contribute towards this increased demand. Despite the high energy demands during competition, orienteers pace themselves such that their mean heart rate remains within the range of 167 to 172 beats/min, despite large fluctuations. The rough terrain encountered in orienteering results not only in a high energy cost but also in a higher incidence of sport-specific injuries, particularly to the ankle. Minor injuries such as cuts and bruises are common during competition.